In search of private partners - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2005)
It is a marriage dictated by necessity: Agricultural research institutes in the South are increasingly teaming up with the private sector to source funding. But these partnerships, geared towards developing profitable products, do little to address ...